Peningkatan Keterampilan Berpikir Kritis Siswa SMAN 1 Tambun Selatan Melalui Permainan Werewolf Card Game - Muhammad Taufik Ramadhani; Yadi Ruyadi Ruyadi; Supriyono Supriyono Supriyono (Ridwan Institute, 2022)
The 21st century is an era that has a major impact on all aspects of human life, especially in the field of education. In order to improve the level of education in accordance with the needs of the system, this research focuses on improving 4C skills, especially critical thinking skills by involving the Werewolf Card Game learning media, which is expected to be a new innovation in the learning process. The method used in this research is descriptive statistics with a quantitative approach. The findings in this study are that there is a strong influence from the use of the Werewolf Card Game learning media on the critical thinking skills of the students of SMA Negeri 1 Tambun Selatan.